An Argument for Administrative Critical Consciousness in Public Administration. (3rd September 2022) - Wright Fields, Christina; Conyers, Addrain
Abstract: Recent public administration scholarship has been challenging the unresponsiveness of leaders due to their unethical and inequitable practices. To address this challenge, this article presents an administrative critical consciousness (ACC) framework to purposefully identify and address societal oppressions. ACC derives from Paulo Freire's critical consciousness and focuses on the ability for individuals to identify and act against an oppressive regime. ACC is a conceptual lens for leaders to acknowledge and intentionally dismantle the longstanding inequities manifested in their institutions and organizations. The authors explore the relationship between engagement, empathy, ethics, and equity in ACC. When administrators utilize an ACC perspective they essentially become more engaged and empathetic, optimistically resulting in more ethical and equitable practices within society. Lastly, the authors describe how ACC occurs when administrators engage in critical consciousness to support and implement transformative action.